Child discipline in Qatar and Palestine: A comparative study of ICAST-R. (November 2016) - Eldeeb, Nehal; Halileh, Samia; Alyafei, Khalid A.; Ghandour, Rula; Dargham, Soha; Giacaman, Rita; Kamal, Madeeha; Imseeh, Sawsan; Korayem, Mona; Nasr, Shiraz; Mahfoud, Ziyad; Abu-Rmeileh, Niveen; et al.
Abstract: To compare the nature and determinants of child discipline in Qatar and Palestine among young adults through retrospective survey to develop legislation, policies and interventions for effective prevention of child maltreatment, and educational materials to promote positive discipline among parents and caregivers. Cross-sectional random household surveys were conducted in each country (Qataris N = 697, Palestinians N = 2064) using ISPCAN Child Abuse Screening Tool-Retrospective (ICAST-R) for young adults (18–24 years), to investigate child discipline methods into the maltreatment range. Qatari young adults were more educated ( p < 0.001) and had more full-time employment ( p = 0.004) than Palestinian young adults. Qatar reported lower physical and emotional abuse compared to their counterparts in Palestine, e.g. Hit/Punch, Kick ( p < 0.001) and Insult/Criticize, Threaten to be hurt/killed ( p < 0.001). Qatari participants found any harsh discipline they received in childhood was not reasonable and not justified compared to Palestinian participants. The more advantaged Qatari population was less likely to experience disciplinary methods that experts developing the ICAST-R defined as abuse compared to Palestinians where the higher incidence of child abuse could be attributed to lower economic advantage, lower level of education and greater exposure to violence. Suggestions are made for future studies in Qatar and Palestine to develop survey methodology with a more culturally appropriate level of intrusion, such as indirect yet meaningful child maltreatment questions.